Motivation-Regulation Strategies of Female and Male Indonesian EFL Undergraduate Students in Thesis Writing - Yonas Yona Anselma; Concilianus Laos Mbato (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2025)
Self-regulation constitutes students’ ability to maintain and manage their efforts to attain specific goals, significantly influencing motivation for thesis writing. Whereas motivation-regulation strategies are correlated with completion rates, a significant gap remains in measuring differences across gender in their use among undergraduate students. Therefore, this study employed a mixed-method study to discover motivation-regulation strategies across gender perspectives and how they used strategies in writing their thesis. The participants of this study were 30 male and 30 female undergraduate students of English Education at Sanata Dharma University, Yogyakarta. This study utilized a closed-ended questionnaire on motivation-regulation strategies and a semi-structured interview to gather the data. The first finding revealed that the undergraduate students were conscious of motivation-regulation strategies: self-consequences, avoidance goals, approach goals, situational interest, and environmental strategy. Further, the second finding indicated a significant difference between female and male students using motivation-regulation strategies at .000 with p < .05. The results implied that gender perspectives affect the students using the motivation-regulation strategies.